Selective influence of host microbiota on cAMP‐mediated ion transport in mouse colon. Issue 6 (10th March 2014) - Lomasney, K. W.; Houston, A.; Shanahan, F.; Dinan, T. G.; Cryan, J. F.; Hyland, N. P.
Abstract More microbes are resident in the distal colon than any other part of the body, and this microbiota has the capacity to influence enteric nerve development, excitability, and gastrointestinal function. Germ‐free (GF) mice are a valuable tool in interrogating the communication between microbiota and host. Despite the intimate relationship which exists between the microbiota and the colonic mucosa–submucosa, there is a paucity of studies examining the influence of the microbiota on secretogogue‐evoked responses. To this end, we investigated both epithelial and neural‐evoked ion transport, and the response elicited by two commensal organisms, in colonic mucosa–submucosa preparations from GF mice in Ussing chambers. Baseline electrical parameters, short‐circuit current and transepithelial resistance, were comparable between tissues from GF and conventional animals. Noteworthy, however, was a hyper‐responsiveness of GF colon to forskolin stimulation. In contrast, the absence of the microbiota did not influence the tissue response to bethanechol. Moreover, responses to the sodium‐channel activator, veratridine, and the TRPV1 receptor agonist, capsaicin were preserved in GF mice relative to conventional tissues. Similarly, the short‐circuit current response to two well‐characterized commensal organisms occurred independent of an interaction with the host microbiota. This is the first comprehensive characterization of secretomotor responses in GF colon.